Shi shi xue lun ji. - Coġjin, author.
1 online resource.
Keywords: "This volume is the masterpiece of Chao Gejin, one of the best-known Chinese scholars of Epic studies, representing his most influential works on the paradigm shift of the Epic across the twentieth century. The discussion ranges from Homeric and Indo-European epics to renewed discoveries of age-old African and Asian epics. The author details developments in research from Parry and Lord's work on Homeric epics and Serbo-Croatian oral poetry to his own research on the Mongol heroic epic. The book traces the formation of theoretical systems such as Oral Formulaic Theory, Ethnopoetics and Performance Theory, and ends with the author's explorations of the 20th-century Mongolian bard Arimpil's singing of his native epic poetry. By combining Chinese traditions and Western theories and methods to demonstrate the fundamentally oral nature of the Homeric epic, Chao brings to light the poetic richness of the still-living Mongol oral epic tradition. Students and scholars of epic studies, literature, folklore and anthropology will find this an essential reference"--